2011
DOI: 10.1159/000329097
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Uric Acid and Subtle Cognitive Dysfunction in Chronic Kidney Disease

Abstract: Background: Elevated serum uric acid has been associated with cognitive dysfunction and vascular cognitive impairment in the elderly. Serum uric acid is also commonly elevated in chronic kidney disease (CKD), but its relationship with cognitive function in these patients has not been addressed. Methods: Subjects with CKD (defined as eGFR <60/ml/min/1.73 m2) were evaluated for cognitive dysfunction using the validated Standardized Mini-Mental State Examination (SMMSE). Individuals with dementia, depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 87 publications
7
41
0
Order By: Relevance
“…Our finding that uric acid relates to worse cognition is supported by most studies [7,24,29,30]. Moreover, of all cognitive domains investigated, we found strongest associations for information-processing speed and executive function.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that uric acid relates to worse cognition is supported by most studies [7,24,29,30]. Moreover, of all cognitive domains investigated, we found strongest associations for information-processing speed and executive function.…”
Section: Discussionsupporting
confidence: 88%
“…Chronic kidney disease is an independent risk factor for cognitive dysfunction and dementia [19]. The findings in the present study are supported by previous studies [18,20,21].…”
Section: Discussionsupporting
confidence: 92%
“…A study by Schretlen et al reported a 2.7-5.9 increased risk of worse results in tests investigating executive functions such as processing speed, verbal memory, and working memory among elderly residents in a nursing home with moderate elevation of uric acid levels 40 . Similar findings were reported in a study on patients with chronic kidney disease 41 , and in the large (n ¼ 1016) cross-sectional InChianti study 42 . In apparent contrast to these pieces of evidence, some studies do not seem to support the hypothesis of the harmfulness of uric acid with regard to cognitive functions.…”
Section: Serum Uric Acid and Dementiasupporting
confidence: 88%